The impact of healthcare-associated infection on mortality: failure in clinical recognition is related with inadequate antibiotic therapy - Cardoso, T. (2013)
Purpose To understand if clinicians can tell apart patients with healthcare-associated infections (HCAI) from those with community-acquired infections (CAI) and to determine the impact of HCAI in the adequacy of initial antibiotic therapy and hospital mortality. Methods One-year prospective cohort study including all consecutive infected patients admitted to a large university tertiary care hospital. Results A total of 1035 patients were included in this study. There were 718 patients admitted from the community: 225 (31%) with HCAI and 493 (69%) with CAI. Total microbiologic documentation rate of infection was 68% (n = 703): 56% in CAI, 73% in HCAI and 83% in hospital-acquired infections (HAI). Antibiotic therapy was inadequate in 27% of patients with HCAI vs. 14% of patients with CAI (p<0.001). Among patients with HCAI, 47% received antibiotic therapy in accordance with international recommendations for treatment of CAI. Antibiotic therapy was inadequate in 36% of patients with HCAI whose treatment followed international recommendations for CAI vs. 19% in the group of HCAI patients whose treatment did not follow these guidelines (p = 0.014). Variables independently associated with inadequate antibiotic therapy were: decreased functional capacity (adjusted OR = 2.24), HCAI (adjusted OR = 2.09) and HAI (adjusted OR = 2.24). Variables independently associated with higher hospital mortality were: age (adjusted OR = 1.05, per year), severe sepsis (adjusted OR = 1.92), septic shock (adjusted OR = 8.13) and inadequate antibiotic therapy (adjusted OR = 1.99). Conclusions HCAI was associated with an increased rate of inadequate antibiotic therapy but not with a significant increase in hospital mortality. Clinicians need to be aware of healthcare-associated infections among the group of infected patients arriving from the community since the existing guidelines regarding antibiotic therapy do not apply to this group and they will otherwise receive inadequate antibiotic therapy which will have a negative impact on hospital outcome.